Analysis of the reflection spectra of MAXI J1535-571 in the hard and intermediate states. Issue 1 (30th May 2022) - Dong, Yanting; Liu, Zhu; Tuo, Youli; Steiner, James F; Ge, Mingyu; García, Javier A; Cao, Xinwu
ABSTRACT: We report results on the joint-fit of the NuSTAR and HXMT data for the black hole X-ray binary candidate MAXI J1535-571. The observations were obtained in 2017 when the source evolved through the hard, hard-intermediate, and soft-intermediate states over the rising phase of the outburst. After subtracting continuum components, X-ray reflection signatures are clearly showed in those observations. By modelling the relativistic reflection in detail, we find that the inner radius R in is relatively stable with R in ≲ 1.55 R g during the three states, which implies that the inner radius likely extends to the innermost stable circular orbit even in the bright hard state. When adopting R in = R ISCO, the spin parameter is constrained to be 0.985_-0.004^+0.002 at 90 per cent confidence (statistical only). The best-fitting results reveal that the inclination of the inner accretion disc is ∼70–74 deg, which notably conflicts with the apparent orientation of the ballistic jet (≤45 deg). In addition, both the photon index and the electron temperature increase during the transition from hard to soft state. It seems that the corona evolves from dense low-temperature in the low/hard state to tenuous high-temperature after the state transition, which indicates that the state transition is accompanied by the evolution of the coronal properties.